VERB FORMATION IN ANGKOLA LANGUAGE - Tina Fitri Siregar and Zainuddin (LINGUISTICA, 2015)
This study deals with the verb formation in Angkol language. This study aims tofind out the kind of affix that formed a verb in Angkola, to describethe pattern ofverb formation in Angkola language and also to find out the grammaticalmeanings occurred through the verb formation in Angkola language. This studywas conducted by using descriptive qualitative method by Moleong (1975:5).Inthis research, the descriptive qualitative method was used to find out the types ofaffixes that formed a verb in Angkola language and to describe the pattern of verbformation in Angkola language. The data of this research were taken from thescript of Parhuta-huta part I movie, and 8 song lyrics of Top SimamoraftDeliana.The technique of data analysis applied was generative morphology proposed byHalle (1973). After analyzing the data it was found that were three kinds of affixesfound in verb-formation of Angkola language, namely: 1). Prefix, such as [di-],[ma-], [mar-], [tar], [pa], [maN-]. 2). Suffix, such as: [-kon], [-i], [-hon]. 3).Confix, such as: [maN-i], [maN-kon] and [mar-an], and morphophonemic changealso occurred through the verb formation of Angkola language, namely: 1).Phonological alteration (assimilation) and 2). Phonological Deletion (Omission).And also found four kinds of grammatical meaning occurred through the verbformation of Angkola language namely: 1. activity, 2. Process, 3. Command, 4.Condition. Therefore the dominant types of affixes occurred in verb formation ofAngkola language is prefix with 6 kinds of prefixes. The findings of this researchshowed that verbs can be formed through a process of affixation whether it comesfrom the verb, noun, adjective, adverbial,